DEVELOPMENT STRATEGY OF EDUCATION CURRICULUM IN STTAL - Risa Apriyani; Adi Bandono; Joko Purnomo; Sunarta Sunarta (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
In the era of the industrial revolution 4.0, the preparation of mastery of maritime technology and the preparation of human resources is the urgency of the Navy's education. STTAL as one of the Navy's educational institutions has a strategic role as a producer of the Navy's human resources capable of merging themselves in technological development. Demands for the development of science and technology that are so fast affect the development of modernization of technology in the rank of maritime technology and graduate qualifications, it is necessary to make adjustments by conducting an evaluation and development in the education curriculum. A concrete step in addressing this requires a strategy to develop STTAL education curriculum in response to scientific vision, efforts to achieve graduate qualifications expected in accordance with societal needs and stakeholder needs. With SWOT analysis, a matrix will be obtained which shows the strengths and weaknesses as well as opportunities and threats which will later be used as a reference to make the right and appropriate strategies.Keywords: SWOT Analysis, STTAL Education Curriculum, Industrial Revolution 4.0